1H-MRS in patients with multiple sclerosis undergoing treatment with interferon β-1a: results of a preliminary study. Issue 2 (1st February 1998) - Sarchielli, P; Presciutti, O; Tarducci, R; Gobbi, G; Alberti, A; Pelliccioli, G P; Orlacchio, A; Gallai, V
Abstract : BACKGROUND: In vivo magnetic resonance spectroscopy (MRS) has been widely used to assess biochemical changes which occur in demyelinating lesions in white matter of patients with multiple sclerosis. It has been suggested that metabolic variations evidenced by MRS are sensitive indicators of the effects of immunomodulatory treatments in this disease.  Given the recent finding of an increase in the disease activity in patients with multiple sclerosis treated with interferon (IFN) β-1a in the first period of treatment, 1 H MRS was used to investigate further the modification in brain metabolic indices, particularly in the first phase of IFN β treatment. METHODS: A 1 H MRS study was performed on five patients with relapsing-remitting multiple sclerosis who were being treated with intramuscular IFN β-1a (6 million units/week) for six months and on five untreated patients. The mean age, duration of the disease, and expanded disability status scores (EDSS) of the two groups were similar. Patients were evaluated at the beginning of the study and in the first, third, and sixth months of treatment. RESULTS: In the multiple sclerosis white matter lesions, N-acetylaspartate (NAA), choline (Cho), inositol (Ins), and creatine (Cr) peaks did not vary significantly over the entire period of the study in the untreated group. In the treated group there was a significant increase in the Cho peak area at the first month compared with the pretreatment period, and this increase continued in the third and sixth months (p<0.001). A slight but not significant rise in the Cho peak was also found in normal appearing white matter in the patient group undergoing treatment with IFN β-1a. The increase in Cho and the lack of significant changes in Cr and NAA peaks induced a significant rise in Cho/Cr and Cho/NAA ratios over the entire period of treatment compared with those at the beginning of the study (p<0.02 and p<0.005 respectively).  In the treated group there was a slight but significant increase in the Ins peak in the first month (p<0.05) but in the third and sixth months of treatment the Ins values returned to the pretreatment range. CONCLUSIONS: IFN β-1a has an impact on metabolite concentrations in multiple sclerosis lesions measured by proton MRS. The increase in Cho, Cho/NAA, and Cho/Cr ratios in multiple sclerosis lesions reinforces the view that they are an index of active or recent demyelination and could support the clinical, neuroradiological and immunological evidence showing an increase in disease activity during the first period of treatment with IFN β-1a. On the other hand, the increase in the Cho peak could be indicative of a rise in membrane turnover in multiple sclerosis lesions or a remodelling of plaques which is not necessarily due to a de novo immune mediated demyelination.